What broke the pearl of the Indian ocean? The causes of the Sri Lankan economic crisis and its policy implications - Samarakoon, Lalith P. (Journal of Financial Stability, 2024)
Sri Lanka unilaterally defaulted on its external debt in April 2022, exposing its long-standing economic and financial vulnerabilities and igniting a series of inter-related multiple economic crises—fiscal, debt, currency, inflation, and balance of payments—as well as a vast socio-political upheaval. This paper analyses the economic crisis and its various dimensions to understand the sources of the crisis and draw policy implications. The role of fiscal balances and public debt in the crisis, along with debt sustainability, international sovereign bonds, liquidity crisis, and currency collapse, are analyzed. The root cause of Sri Lanka’s economic crisis was running persistent and large fiscal deficits, which were increasingly financed by unsustainable public debt, particularly foreign commercial borrowings. A substantial reduction and reprofiling of debt through restructuring of both domestic and foreign debt to ensure debt sustainability, meaningful fiscal policy reforms anchored by revenue increases and expenditure rationalization to reduce fiscal deficits, and deep growth-enhancing structural reforms are necessary for medium-term rescue and recovery and long-term growth and stability of Sri Lanka. The findings provide important policy lessons for other emerging markets and middle-income economies.